Hydroa vacciniforme-like cutaneous T-cell lymphoma - Jian-Qiang Shi; Qiu-Xia Chen; Shun-Fan Li; Wen Li (Wolters Kluwer Medknow Publications, 2014)
A 14-year-old Chinese girl had a 6-year history of recurrent lesions on her head, face, and limbs. Epstein-Barr virus (EBV)-IgM was positive. Histopathological findings revealed focal lymphocyte invasion in subcutaneous panniculus adiposus, mainly surrounding the blood vessels. Immunohistochemistry showed CD3+, CD4+, CD5+, CD8+, TIA-1+, GrB+, CD56-, and L26-. In situ hybridization staining for EBV-encoded small nonpolyadenylated RNA (EBER)-1 was positive. The patient showed significant improvement in clinical symptoms after being treated with acyclovir and IFN-α in this patient.